Per- and polyfluoroalkyl substances and kidney function: Follow-up results from the Diabetes Prevention Program trial. (March 2021) - Lin, Pi-I D.; Cardenas, Andres; Hauser, Russ; Gold, Diane R.; Kleinman, Ken P.; Hivert, Marie-France; Calafat, Antonia M.; Webster, Thomas F.; Horton, Edward S.; Oken, Emily
Highlights: We examined the relationship between PFAS and eGFR among prediabetic adults. We found evidence of associations between plasma PFAS and adverse kidney function. Baseline plasma PFAS was inversely associated with prospective measures of eGFR. Lifestyle intervention did not modify the association. We observed stronger effect among those with baseline hypertension. Abstract: Per- and polyfluoroalkyl substances (PFAS) are ubiquitously detected in populations worldwide and may hinder kidney function. The objective of the study was to determine longitudinal associations of plasma PFAS concentrations with estimated glomerular filtration rate (eGFR) and evaluate whether a lifestyle intervention modify the associations. We studied 875 participants initially randomized to the lifestyle or placebo arms in the Diabetes Prevention Program (DPP, 1996–2002) trial and Outcomes Study (DPPOS, 2002–2014). We ran generalized linear mixed models accounting a priori covariates to evaluate the associations between baseline PFAS concentrations and repeated measures of eGFR, separately, for six PFAS (PFOS, PFOA, PFHxS, EtFOSAA, MeFOSAA, PFNA); then used quantile-based g-computation to evaluate the effects of the six PFAS chemicals as a mixture. The cohort was 64.9% female; 73.4% 40–64 years-old; 29.4% with hypertension; 50.5% randomized to lifestyle intervention and 49.5% to placebo and had similar plasma PFAS concentrations as the general U.S. population in 1999–2000. Most participants had normal kidney function (eGFR > 90 mL/min/1.73 m 2 ) over the approximately 14 years of follow-up. We found that plasma PFAS concentrations during DPP were inversely associated with eGFR during DPPOS follow-up. Each quartile increase in baseline plasma concentration of the 6 PFAS as a mixture was associated with 2.26 mL/min/1.73 m 2 lower eGFR (95% CI: −4.12, −0.39) at DPPOS Year 5, approximately 9 years since DPP randomization and PFAS measurements. The lifestyle intervention did not modify associations, but inverse associations were stronger among participants with hypertension at baseline. Among prediabetic adults, we found inverse associations between baseline plasma PFAS concentrations and measures of eGFR throughout 14 years of follow-up. The lifestyle intervention of diet, exercise and behavioral changes did not modify the associations, but persons with hypertension may have heightened susceptibility.